2014
DOI: 10.1079/pavsnnr20138053
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency and optimization of nitrogen fertilization in conservation agriculture.

Abstract: The International Maize and Wheat Improvement Center, known by its Spanish acronym, CIMMYT® (www.cimmyt.org), is a not-for-profit research and training organization with partners in over 100 countries. The center works to sustainably increase the productivity of maize and wheat systems and thus ensure global food security and reduce poverty. The center's outputs and services include improved maize and wheat varieties and cropping systems, the conservation of maize and wheat genetic resources, and capacity buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 0 publications
0
22
1
2
Order By: Relevance
“…In addition, intercrops with N 2 -fixing legumes may reduce the C:N ratio of the resulting mulch mixture. The decomposition of this mulch will release nitrogen, as opposed to the decomposition of high C:N materials such as maize stalks, which require that soil microbes use the available N for their own metabolic needs resulting in temporary N immobilisation (Giller et al, 2011;Grahmann et al, 2013). This may explain our finding of increased available N in the sole cowpea and intercrop plots.…”
Section: Maizecowpea Intercrops and Over-yieldingmentioning
confidence: 84%
“…In addition, intercrops with N 2 -fixing legumes may reduce the C:N ratio of the resulting mulch mixture. The decomposition of this mulch will release nitrogen, as opposed to the decomposition of high C:N materials such as maize stalks, which require that soil microbes use the available N for their own metabolic needs resulting in temporary N immobilisation (Giller et al, 2011;Grahmann et al, 2013). This may explain our finding of increased available N in the sole cowpea and intercrop plots.…”
Section: Maizecowpea Intercrops and Over-yieldingmentioning
confidence: 84%
“…The N use efficiency and yield levels in the present study may be associated with; (1) the adoption of long known strategies to increase N use efficiency, (2) a non-critically limiting N supply for the crop, provided in part by soil mineralization under a mature conservation agriculture system, and a possible synergy among these two factors. Grahmann et al (2013) [12] suggested an initial short-term N immobilization period under conservation agriculture, but steady N mineralization rates afterward. In support of the hypothesis that wheat in this study grew on a relatively N rich environment, not only through applied fertilizers, the following evidence is presented.…”
Section: Discussionmentioning
confidence: 99%
“…Soil coverage with harvest waste -basic component of conservation agriculture practices-favors immobilization by the N applied with the chemical fertilizer (Grahmann et al, 2013), specially during the second fertilization when it stays in direct contact with the organic material because tillage is not performed and N cannot stay underground. Thus, microbial biomass uses part of the N supplied for its metabolism during organic matter decomposition.…”
Section: Crop Rotation Assaymentioning
confidence: 99%